Halal research streams: A systematic and bibliometrics review - Prakoso Bhairawa Putera; Tiurma Melissa Rakhel (Cogent Social Sciences)
This paper aims to provide a bibliometric meta-analysis of the already substantial and growing literature on the Halal industry. This research uses HistCite and VosViewer software to conduct a bibliometric analysis based on publications on Web of Science data from the beginning of the appearance of halal articles up to 2023. The analysis results indicated six research streams regarding Halal literature: Consumer Behavior, Islamic Branding, Islamic Marketing, Halal Supply Chain, Halal Certification, and Halal Tourism. In addition, this article discusses the Evolution of Halal Research Streams, namely, the pattern of changes that occur in each phase based on the year of publication to identify and compare whether there have been changes in research streams, theory, and methodology used. This paper identifies and analyzes trending articles at the end of the period in which this metadata is collected. The aim is not only to provide insight regarding the origins of the topic of industrial halal origin but also to identify topics that will emerge in the future. Finally, this paper provides information and suggestions for future halal topics divided according to research streams. [Figure: see text]